PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN MELALUI PENERAPAN STRATEGI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS VII SMTK - Anggrini Amelia Wongkar; Yuel Sumarno; Rini (Edukasi : Jurnal Pendidikan Agama Kristen, 2020)
Improving the Quality of Christian Education Learning through the Implication of Contextual Teaching and Learning Strategy In Class VII Students of Bethel Christian Middle School Jakarta. Christian Education Learning is a required learning that has to exist in every education level, because of the importance of spiritual value in those learning. However, in its development, religious education lessons are less qualified in terms of where the students only receive more information than capture the meaning of the learning so that they are less able to apply the values ​​of Christian education learning. This study aims to improve the Quality of Christian Religious Education Learning through the Implementation of Contextual Teaching and Learning Strategies for Class VII Students of Bethel Christian Middle School Jakarta, which is then written at Bethel Indonesia Theological College. The application of CTL learning strategies in Christian Education learning can improve the quality of Christian Education learning itself, from 11.50% in the initial conditions to 92.30% in the final condition. The Christian Education learning material increased from 0.76% in the initial condition to 92.30% in the final condition. For Christian Education teacher skills there are 0.76% (low qualification), 92.3 (sufficient qualification), 0.00% (good qualification), so that from 0.00% the initial condition becomes 92.30% in the final condition. In student learning activities in Christian Education learning from 30.70% in the initial condition to 76.90% in the final condition.